2020
DOI: 10.3390/cells9081798
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors, and Cytokines; Understanding the Role of Tyrosine Phosphatase SHP2 in Gametogenesis and Early Embryo Development

Abstract: Growth factors and cytokines have vital roles in germ cell development, gamete maturation, and early embryo development. Cell surface receptors are present for growth factors and cytokines to integrate with and trigger protein signaling in the germ and embryo intracellular milieu. Src-homology-2-containing phosphotyrosine phosphatase (SHP2) is a ubiquitously expressed, multifunctional protein that plays a central role in the signaling pathways involved in growth factor receptors, cytokine receptors, integrins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…Focal adhesion plays vital roles in cell growth, death, cell cycle progression, cell proliferation, differentiation and repair [ 41 , 42 ]. Cytokines are small molecular peptides that regulate cell functions and are essential in regulation of germ cell development, gametogenesis, gamete maturation [ 43 ], development of the testis and its normal function [ 44 ], physiological processes of the ovarian reserve, cell proliferation/differentiation folliculogenesis, and oocyte maturation [ 45 ]. In addition, cytokines create an immunologically permissive nutritional environment for embryonic development and are an important basis for reproductive success [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion plays vital roles in cell growth, death, cell cycle progression, cell proliferation, differentiation and repair [ 41 , 42 ]. Cytokines are small molecular peptides that regulate cell functions and are essential in regulation of germ cell development, gametogenesis, gamete maturation [ 43 ], development of the testis and its normal function [ 44 ], physiological processes of the ovarian reserve, cell proliferation/differentiation folliculogenesis, and oocyte maturation [ 45 ]. In addition, cytokines create an immunologically permissive nutritional environment for embryonic development and are an important basis for reproductive success [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…SHP2 is a nonreceptor protein tyrosine phosphatase encoded by the protein tyrosine phosphatase nonreceptor type 11 gene (PTPN11) ( Kong & Long 2022 ). SHP2 is widely expressed and plays a key role in cell growth, survival, proliferation, differentiation, and migration ( Idrees et al 2020 ). In most cases, SHP2 is necessary for the Ras–ERK and PI3K–Akt pathways and plays a dynamic role in gametogenesis, embryo maturation, and embryonic development ( Idrees et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors, a group of peptides such as endothelial growth factor and insulin-like growth factor (IGF), play vital roles in germ cell development, gamete maturation and early embryo development (Breier et al, 1992;Ferrara, 1999;Idrees et al, 2020). Studies showed that TCM-induced reproductive toxicity was connected by modulating the expression and signal transduction of growth factors.…”
Section: Growth Factorsmentioning
confidence: 99%